Early and sustained blood pressure control is necessary for stroke prevention - Chrysant, Steven G. (Journal of Thoracic Disease, 2015)
Hypertension is the most common and most important risk factor for coronary artery disease (CAD), heart failure (HF), chronic kidney failure (CKD), and especially stroke, if left untreated. Stroke is a devastating complication of hypertension and is a major cause of death and disability worldwide and its incidence increases linearly with the blood pressure (BP) and level and the advancement of age (1-3). Lewington et al., have shown that the incidence of stroke was directly related to the level of systolic and diastolic BP (SBP, DBP) for all age groups, but with higher prevalence in older than younger subjects (3). Stroke, besides being a cause of long-term disability for the affected person, it is also a significant burden on society and healthcare expenditures (4). According to this report, each year approximately 795,000 people experience a new or recurrent stroke, with 610,000 being first strokes and 185,000 recurrent strokes with 87% of all strokes being ischemic and 10% being hemorrhagic. The direct and indirect expenditures in the US for the year 2012 were $71.6 billion (4), and it is projected that by the year 2030, the total stroke-related, medical costs to be $183.13 billion, with the majority of the projected increase to arise from those 65-79 years of age (5). Stroke is the third leading cause of death in the in the US after ischemic heart disease (IHD) and cancer. Worldwide in 2010, the prevalence of stroke was 33 million with 16.9 million people having a first stroke and stroke was the second-leading global cause of death behind IHD (6). Possible causes for this increase in stroke incidence are the ageing of the population, the poor control of BP as well as the other cardiovascular risk factors, like obesity, diabetes mellitus and hyperlipidemia (5-7). However, recent studies show that the incidence of ischemic and hemorrhagic strokes has decreased significantly between 1990 and 2010 by 13% and 19% respectively, in high income countries, but not in low to middle income countries (7). This could, possibly, reflect the better control of BP and other risk factors in the high income countries.